2021
DOI: 10.1136/bmjopen-2020-047567
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the COVID-19 pandemic and related control measures on cancer diagnosis in Catalonia: a time-series analysis of primary care electronic health records covering about five million people

Abstract: ObjectiveCancer care has been disrupted by the response of health systems to the COVID-19 pandemic, especially during lockdowns. The objective of our study is to evaluate the impact of the pandemic on the incidence of cancer diagnoses in primary care.DesignTime-series study of malignant neoplasms and diagnostic procedures, using data from the primary care electronic health records from January 2014 to September 2020.SettingPrimary care, Catalonia, Spain.ParticipantsPeople older than 14 years and assigned in on… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
60
7
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(91 citation statements)
references
References 49 publications
15
60
7
2
Order By: Relevance
“…The most likely explanation for this delayed drop in CRC incidence, is that the already scheduled colonoscopies for individuals with a positive FIT were not cancelled. The drop in CRC incidence in the Netherlands was similar to the observed drop in CRC incidence in Catalonia (Spain) and in a teaching hospital in Paris (France) where a reduction of 38% and 30%, respectively, in the period March till June 2020 were reported (11,15). The relative reduction in diagnoses of CRC observed in our study was smaller than the reduction in CRC diagnoses in the UK (8).…”
Section: Discussionsupporting
confidence: 76%
“…The most likely explanation for this delayed drop in CRC incidence, is that the already scheduled colonoscopies for individuals with a positive FIT were not cancelled. The drop in CRC incidence in the Netherlands was similar to the observed drop in CRC incidence in Catalonia (Spain) and in a teaching hospital in Paris (France) where a reduction of 38% and 30%, respectively, in the period March till June 2020 were reported (11,15). The relative reduction in diagnoses of CRC observed in our study was smaller than the reduction in CRC diagnoses in the UK (8).…”
Section: Discussionsupporting
confidence: 76%
“…Similar to the results from the above studies, we found a steep decline in weekly procedure volumes early in the pandemic, persisting in lower proportions for the rest of the year. An assessment of monthly numbers of mammograms and colonoscopies from PC healthcare registries in Catalonia showed a reduction of 66% and 65%, respectively, during lockdown, persisting for colonoscopies in a lower proportion (23%) in the post-lockdown period July-September 2020 [15]. To our knowledge, no study has described the impact on diagnostic procedures stratified by waiting times.…”
Section: Discussionmentioning
confidence: 97%
“…Using population-based e-health registries from PC, a recent report recounted a 34% reduction in the incidence rates of cancer during the COVID-19 period March-September 2020 in Catalonia. Although the study reported the degree of change in the volume of mammograms and colonoscopies performed during this period, other diagnostic tests were not mentioned [15].…”
Section: Introductionmentioning
confidence: 99%
“…Entre los errores que más aumentaron destacan los relacionados con las citas, los problemas de comunicación y el diagnóstico; lo cual encaja con un contexto de atención no presencial donde la comunicación es menos fluida y los diagnósticos más complicados al carecer de la valoración presencial del paciente. En este sentido, varios estudios refieren el impacto negativo de la pandemia en el seguimiento y control de enfermos crónicos 19 , en el manejo de pacientes con dolor crónico 20 y en los nuevos diagnósticos de enfermedades 21 , 22 , 23 , 24 . Un estudio reciente en 21 CS de Reino Unido pone de manifiesto la preocupación de los profesionales de la salud por el mayor riesgo clínico que entraña el modelo de consulta no presencial impuesto durante la pandemia 25 .…”
Section: Discussionunclassified